2019
DOI: 10.7759/cureus.4293
|View full text |Cite
|
Sign up to set email alerts
|

Can Platelet Indices Reduce Negative Appendectomy Rates?

Abstract: Introduction The role of whole blood count parameters in the diagnosis of diseases in which inflammatory processes play a role is one of the more frequently mentioned topics in the literature in recent years. Studies of acute appendicitis have also been carried out in this regard, but studies focused on platelet parameters are few and contradictory. We aimed to investigate the role of mean platelet volume (MPV) and platelet distribution width (PDW) in the diagnosis of acute appendicitis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 27 publications
(35 reference statements)
0
15
1
2
Order By: Relevance
“…The initial search identified a total of 101 potential articles. After screening, nine articles that matched the researchers’ criteria were deemed suitable for inclusion in the meta-analysis [ [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] ]. The PRISMA diagram used in the search process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The initial search identified a total of 101 potential articles. After screening, nine articles that matched the researchers’ criteria were deemed suitable for inclusion in the meta-analysis [ [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] ]. The PRISMA diagram used in the search process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies [ [21] , [22] , [23] , 25 , 25 , 27 , 29 ] reported an association between MPV and acute appendicitis, with a total of 2142 patients (1406 patients [68%] in the acute appendicitis group and 736 patients [32%] in the control group). Pooled analysis of the seven studies demonstrated that the MPV among patients with acute appendicitis was significantly lower than the control group (OR = −0.81,95% CI = −1.51 to −0.11, P = 0.02).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations